Myopia: An ounce of prevention is worth a pound of cure - Bullimore, Mark A.; Brennan, Noel A. (Ophthalmic & physiological optics, 2023)
Purpose Myopia severity has a profound impact on visual impairment in later life. A patient's final level of myopia may be lowered by myopia control, but also by delaying onset. Here, we evaluate the influence of the age of onset on the final recorded level of myopia. Methods Data were extracted from: (1) Three prospective cohort studies of myopia progression in East Asia and the United States where the final recorded level of myopia is presented as a function of the established age of onset. (2) Four retrospective studies of myopia progression in Finland, India, the Netherlands and China and two cross‐sectional studies in Argentina and the UK where the age of onset was based on self‐report of age at first spectacle prescription. (3) A cohort study of Finnish subjects originally recruited for a clinical trial and followed into adulthood. Subjects were divided into five groups according to age at recruitment that was used as a surrogate for the age of onset. Results Final recorded level of myopia was plotted as a function of age of onset for all studies. Among the three East Asian studies, the slopes are between 0.68 and 0.97 D/year, meaning that each later year of onset is associated with between 0.68 and 0.97 less myopia at the final recorded refraction. For six of the seven non‐East Asian studies, the slopes are substantially flatter, with slopes between 0.23 and 0.50 D/year. By contrast, the slope for the Finnish study was 0.87 D/year. Increasing age of final recorded refraction tended to be associated with higher levels of myopia. Conclusion Among East Asians, delaying the onset of myopia by 1 year has the potential to lower the final myopia level by 0.75 D or more—equivalent to 2–3 years of myopia control with existing modalities. The benefit is lower, but meaningful, among non‐East Asians.